2022
DOI: 10.3389/fpsyg.2022.988609
|View full text |Cite
|
Sign up to set email alerts
|

“Hot” executive functions are comparable across monolingual and bilingual elementary school children: Results from a study with the Iowa Gambling Task

Abstract: Past research found performance differences between monolingual and bilingual children in the domain of executive functions (EF). Furthermore, recent studies have reported advantages in processing efficiency or mental effort in bilingual adults and children. These studies mostly focused on the investigation of “cold” EF tasks. Studies including measures of “hot” EF, i.e., tasks operating in an emotionally significant setting, are limited and hence results are inconclusive. In the present study, we extend previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 110 publications
0
1
0
Order By: Relevance
“…Prior research has mostly focused on generally developing children or adults, with less consideration for persons with unique educational needs. A study conducted by Enke et al (2022) analyzed the executive functions of bilingual and monolingual children with and without language impairment. The study revealed that bilingual children with language impairment exhibited superior executive function performance in comparison to monolingual children with similar language deficits.…”
Section: Literature Review and Previous Studiesmentioning
confidence: 99%
“…Prior research has mostly focused on generally developing children or adults, with less consideration for persons with unique educational needs. A study conducted by Enke et al (2022) analyzed the executive functions of bilingual and monolingual children with and without language impairment. The study revealed that bilingual children with language impairment exhibited superior executive function performance in comparison to monolingual children with similar language deficits.…”
Section: Literature Review and Previous Studiesmentioning
confidence: 99%
“…In contrast, hot EFs often refer to tasks that are assessing decision-making using rewards (e.g., digital points, fictional money). While there are several studies investigating cool EFs in children exposed to or using more than one language (e.g., van den Noort et al, 2019 ), to our knowledge, there is only one instance where hot EF was studied through the context of decision-making which was conducted in monolingual and bilingual children (Enke et al, 2022 ). The period between preschool and late childhood is of particular interest as it precedes adolescence, a phase of differential developmental trajectories for hot and cool EFs (Poon, 2017 ), and changes in problem-solving, risk-taking (Casey et al, 2008 ; Mills et al, 2014 ; Crone et al, 2016 ) and decision-making (Blakemore and Robbins, 2012 ).…”
Section: Introductionmentioning
confidence: 99%